Los patrones de asentamiento del Periodo Intermedio Temprano en Palpa, costa sur del Perú - Soßna, Volker (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The Nasca culture developed on the Peruvian South Coast roughly between 200 B. C. and 650 A. D. from the preceding Paracas culture. However, the circumstances of its rise, crisis and ultimate decline as well as its political organization are still subject to controversial debate among scholars. In the highly sensible arid environment, climate changes may have triggered, or at least influenced, major cultural developments. Especially the choice of sites for settlements depended on the availability of water and cultivable land but in times of conflict also on defensive needs. In order to gain new insights into the past, not only more archaeological data is needed; it is also essential to interpret new and existing findings against the background of environmental studies. Between 1997 and 2010 the German Archaeological Institute documented a vast number of archaeological sites by prospection and excavation in the Northern part of the Río Grande de Nasca drainage. At the same time, geographers from the University of Heidelberg investigated the history of climate in the same region. Both sets of data can now be compared and merged into a broader model. In the present article, almost 450 settlements from the Nasca culture as well as from the preceding Late Paracas culture and the following Middle Horizon are analyzed to address the question how settlement patterns, political organizations and population levels changed over time. Wherever possible, published settlement data from neighbouring projects was considered as well. It seems that until the Early Nasca phase there was a constant population growth and a trend towards political integration which was not significantly influenced by climate. But during Middle Nasca Times a general crisis triggered mayor population shifts and a decentralization of political power. It seems highly likely that a long lasting process of decreasing precipitation in the mountains led to repeated and prolonged shortages of irrigation water in the fertile flood plains of the river valleys and therefore to a severe crisis in food production. In the article, I argue that for this reason people had to migrate in large numbers and that the remaining population increasingly depended on imports from the more stable highland regions. This process resulted in a growing cultural and political influence of the Wari culture and fi nally into the formal integration of the Nasca heartlands into the Wari realm.The article will be available as a PDF in the near future.